Post-Materialism Influencing Total Entrepreneurial Activity Across Nations - Lorraine Uhlaner; A. Roy Thurik (Max Planck Institute for Research into Economic Systems, 2005)
The study of predictors of entrepreneurial activity at the country level has been dominated by economic influences. However, the relative stability of differences in entrepreneurial activity across countries suggests that other forces such as institutional and/or cultural factors are at play. The objective of this paper is to explore more specifically how post-materialism may help to explain differences in entrepreneurial activity across countries. A distinction is made between nascent entrepreneurship, new business formation and a combination of the two, referred to as total entrepreneurial activity, as defined within the Global Entrepreneurship Monitor. The model is also tested for the rate of established businesses, as distinct from nascent and young firms. The measure for post-materialism is based upon Inglehart's four-item post-materialism index. Because of the known interactions between economic, cultural, and social factors found in previous research, a set of economic, demographic and social factors is included to investigate the independent role post-materialism plays in prediction of entrepreneurial activity levels. In particular, per capita income is used to control for economic effects. Education rates at both secondary and tertiary levels are used as demographic variables. Finally, life satisfaction is included to control for social effects. Data from 27 countries, world-wide, are used to test the hypotheses, based on intersecting data available from the Global Entrepreneurship Monitor, World Values Survey and other published sources. Findings confirm the significance of post-materialism in predicting total entrepreneurial activity and more particularly, new business formation rates, even when controlling for these other factors.
Keywords: O57; P52; O11; M13; Z1; 330; comparative analysis of economies; entrepreneurship; self-employment; macro-economic analyses of economic development; Unternehmer; Postindustrielle Gesellschaft; Soziale Werte; Kulturpsychologie; Entwicklungsstufe; Schätzung; Welt